2019
DOI: 10.5194/isprs-archives-xlii-2-w9-787-2019
|View full text |Cite
|
Sign up to set email alerts
|

3d Modeling for Rock Art Documentation Using Lightweight Multispectral Camera

Abstract: <p><strong>Abstract.</strong> This paper discusses the use of the lightweight multispectral camera to acquire three-dimensional data for rock art documentation application. The camera consists of five discrete bands, used for taking the motifs of the rock art paintings on a big structure of a cave based on the close-range photogrammetry technique. The captured images then processed using commercial structure-from-motion photogrammetry software, which automatically extracts the tie point. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Recently, the use of commercial digital cameras employing CCD (charge-coupled device) and CMOS sensors, modified for near-infrared or full-spectrum acquisition (combined with external NIR filters) has been commonized in heritage science. They consist of lower cost, high-resolution alternatives with spectral imaging capabilities, which retain user-friendly features and interfaces to a broad variety of photographic accessories and software [18][19][20][21][22].…”
Section: Near-infrared Imaging and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the use of commercial digital cameras employing CCD (charge-coupled device) and CMOS sensors, modified for near-infrared or full-spectrum acquisition (combined with external NIR filters) has been commonized in heritage science. They consist of lower cost, high-resolution alternatives with spectral imaging capabilities, which retain user-friendly features and interfaces to a broad variety of photographic accessories and software [18][19][20][21][22].…”
Section: Near-infrared Imaging and Modelingmentioning
confidence: 99%
“…The availability of high-resolution, easily operated digital cameras for NIR acquisition, in combination with SfM/MVS image-based modeling techniques, has made feasible the 3D spectral modeling for heritage applications. Contemporary research, which showed promising results [22][23][24][25][26][27][28], led us to the motivation for further experimentation.…”
Section: Near-infrared Imaging and Modelingmentioning
confidence: 99%
“…Mathys et al reconstructed the object’s surface by using the VIS-R _VIS images and processed the MSI texture mapping by replacing the colour images with the single spectral band images to generate 16 different MSI texture models [ 34 ]. Zainuddin et al used a Micasense RedEdge multispectral camera with five different spectral images for the 3D spectral documentation of rock art [ 35 ]. Nocerino et al mapped colour images and UV-induced visible luminescence images via a photogrammetric workflow on the 3D surface captured with a structured light scanner [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…TP includes a wide range of techniques applicable to historic art examination [15]. Specifically, near-infrared (NIR) imaging has been implemented to enhance archaeological observation [16], to determine the state of conservation of buildings [17], to inspect mural paintings [18], to assist the identification of pigments [19], to investigate underdrawings of panel paintings [20], underprintings [21], and palimpsests [22], to examine rock art [23], and to study feature characteristics of painted artifacts [24]. Applications of integrated heritage CRP and TP can be found in recent bibliography, showcasing a promising combination that should be further evaluated.…”
Section: Introductionmentioning
confidence: 99%